21st Century illiberal democracies in Latin America and the Inter-American Democratic Charter: Two models of democracy in the region? - Daniel Soria Luján (Derecho PUCP, 2015)
The Inter-American Democratic Charter (IDC) was adopted in 2001 by member states of the Organization of American States (OAS) as a renewed instrument for the defense of democracy, not only against traditional coup d´etat but also to face serious violations to horizontal accountability. The second assumption took into consideration, as a precedent, the political situation in Peru during Alberto Fujimori's administration (1995-2000), defined as a competitive authoritarian regime by Political Science and Constitutional Law scholars. However, during the last decade to the presentwe find in Latin America several countries with governments where the principle of checks and balances has been eroded as a result of measures adopted by their respective executive branch. This situation suggests the following concerns: The liberal democratic model of the IDC is in crisis? This model has been overcame by illiberal governments that privileges economic and social rights and restraints civil and political rights? Or both models a recondemned to coexist in the region?